Austeridade ou austericídio? : uma discussão sobre as políticas de ajuste econômico nos piigs e no Brasil na última década - Machado, Jerônimo de Moraes (2018)
This master thesis, based on an historical contextualization of the capitalist system and its crises, analyzed more closely the causes, consequences and policies of confrontation that the PIIGS and Brazil used in relation to the global crisis that began in 2007/2008 and the possibility of reaching the objectives of the Agenda 2030 for Sustainable Development by these countries, all signatories of the Agenda. Metodologically, the study was based on the dialectical-critical method, both through qualitative and bibliographic exploratory review and data analysis. Initially, was carried out an historical contextualization of capitalism, from the beginning of Mercantilism until the end of the 20th century. Then the attention was focused on the causes of the current crisis, and were discussed the liberal, the Keynesian and the neoliberal theories. In the following chapter, were analyzed the reactions of the PIIGS governments to the crisis and the consequences of these policies. In the last development chapter, the Brazilian case was verified. Despite its success in dealing with the global crisis in its early years, the country had problems in the following years. It was concluded that the reactions of governments, both in Europe and Brazil, were to nationalize private debts to save the financial system from bankruptcy. This way, there were spending and investments cuts both economically and socially in strategic sectors, harming the populations in social vulnerability - selective fiscal austerity. The results of the policies of confrontation were the deepening of the economic crisis in the "real side" of the economy, the increase of the inequality and the worsening of the less favored classes life conditions.